Teoria da mente e empatia: um estudo com crianças pré-escolares - Paludeto, Simone Priscila (2016)
The theory of mind and empathy are important socio-cognitive skills whose theoretical boundaries are not clearly defined. These skills develop gradually in children, and are essential to everyday interactions and children's social learning. Thus, we find it relevant to study the relationship between the development of theory of mind and empathy, as these two skills are important dimensions of social-emotional development and children's social-cognitive. The main objective of this research was to investigate the associations between theory of mind and empathic ability in children during early childhood education. Thus, our study aims to investigate the relationship between theory of mind and empathy as integral parts of social cognitive development. Participants in this study included 40 children aged between 3 and 6 years. Children's performance in tasks theory of mind and empathy, quantitatively and qualitatively, was analyzed by age group. Children were considered to be 3, 4, 5 and 6 years, descriptively, and then two groups of 3 and 4 years and 5 and 6 years. The second analysis was performed using the Student T test. Analysis of correlation between theory of mind and empathy with the Pearson test was performed. The results showed the existence of a correlation between empathy and theory of mind, although not statistically significant, except in relation to the false belief task. Also, we could see a correlation in our study between better performance of children in theory of mind and empathy with increasing age of the child